American Press Association correspondence - American Press Association
Correspondence addressed primarily to the managing editors of the American Press Association from writers of stories and articles relating to the publication of their material or to other literary matters. Also includes several letters from managing editors of the association's branch offices. Correspondents include John Aulde, L.H. Bailey, Rolla C. Carpenter, William Eleroy Curtis, Charles A. Custis, Allan Forman, Moses P. Handy, John Langdon Heaton, Bart Kennedy, Alfred E. Lee, Lida Rose McCabe, Hiram Powers, John Gilmer Speed, Ainsworth Rand Spofford, Kate Jordan Vermilye, Rufus Rockwell Wilson, John Russell Young.
Collection material in English.
Keywords: Aulde, John -- Correspondence; Bailey, L. H. -- 1858-1954 -- Correspondence; Carpenter, Rolla C. -- 1852-1919 -- Correspondence; Curtis, William Eleroy, -- 1850-1911 -- Correspondence; Custis, Charles A. -- Correspondence; Forman, Allan, -- 1860-1914 -- Correspondence; Handy, Moses P. -- 1847-1898 -- Correspondence; Heaton, John Langdon, -- 1860-1935 -- Correspondence; Kennedy, Bart, -- 1861-1930 -- Correspondence; Lee, Alfred E. -- 1838- -- Correspondence; McCabe, Lida Rose, -- 1865-1938 -- Correspondence; Powers, Hiram, -- 1805-1873 -- Correspondence; Speed, John Gilmer, -- 1853-1909 -- Correspondence; Spofford, Ainsworth Rand, -- 1825-1908 -- Correspondence; Vermilye, Kate Jordan, -- -1926 -- Correspondence; Wilson, Rufus Rockwell, -- 1865-1949 -- Correspondence; Young, John Russell, -- 1840-1899 -- Correspondence; American literature; Journalism -- United States -- Societies, etc